RIP140 contributes to foam cell formation and atherosclerosis by regulating cholesterol homeostasis in macrophages. (February 2015) - Lin, Yi-Wei; Liu, Pu-Ste; Adhikari, Neeta; Hall, Jennifer L.; Wei, Li-Na
Abstract: Atherosclerosis, a syndrome with abnormal arterial walls, is one of the major causes that lead to the development of various cardiovascular diseases. The key initiator of atherosclerosis is cholesterol accumulation. The uncontrolled cholesterol deposition, mainly involving low-density lipoprotein (LDL), causes atheroma plaque formation, which initiates chronic inflammation due to the recruitment of inflammatory cells such as macrophages. Macrophages scavenge excess peripheral cholesterol and transport intracellular cholesterol to high-density lipoprotein (HDL) for excretion or storage. Cholesterol-laden macrophage-derived foam cell formation is the main cause of atherogenesis. It is critical to understand the regulatory mechanism of cholesterol homeostasis in the macrophage in order to prevent foam cells formation and further develop novel therapeutic strategies against atherosclerosis. Here we identified a protein, RIP140 (receptor interacting protein 140), which enhances macrophage-derived foam cell formation by reducing expression of reverse cholesterol transport genes, A TP-binding membrane cassette transporter A-1 (ABCA1) and ATP-binding membrane cassette transporter G-1 (ABCG1). In animal models, we found that reducing RIP140 levels by crossing macrophage-specific RIP140 knockdown (MϕRIP140KD) mice with ApoE null mice effectively ameliorates high-cholesterol diet-induced atherosclerosis. Our data suggest that reducing RIP140 levels in macrophages significantly inhibits atherosclerosis, along with markers of inflammation and the number of macrophages in a western diet fed ApoE null mouse. This study provides a proof-of-concept for RIP140 as a risk biomarker of, and a therapeutic target for, atherosclerosis. Graphical abstract: Highlights: RIP140 promotes macrophage-derived foam cell formation. RIP140 suppresses LXR-regulated expression of ABCA1 and ABCG1. Lowering RIP140 level in macrophage ameliorates atherosclerosis.